Impact of interleukin 6 promoter polymorphisms (−174 G > C, −572 G > C and −597 G > A) on plasma IL-6 levels and their influence on the development of DVT: a study from India. Issue 10 (26th November 2018) - Sharma, Amit; Singh, Kanwaljeet; Biswas, Arijit; Ranjan, Ravi; Kishor, Kamal; Pandey, Hareram; Kumar, Ravi; Mahapatra, Manoranjan; Oldenburg, Johannes; Saxena, Renu
ABSTRACT: Objectives: To evaluate the association of interleukin 6 ( IL-6) levels with deep vein thrombosis (DVT) and to assess the impact of IL-6 promoter polymorphisms (−174G > C, −572G > C and −597G > A) on its plasma levels and their influence in the development of DVT in India. Methods: One hundred DVT patients and 100 age and sex-matched healthy controls were study subjects. IL-6 polymorphisms were identified by polymerase chain reaction-restriction fragment length polymorphism. IL-6 levels were detected by enzyme-linked immunosorbent assay. Results: Significantly raised IL-6 levels were observed in patients as compared to controls. (Patients: 13.73 ± 6.30 pg/ml, Controls: 11.83 ± 4.47 pg/ml, p  = 0.014). The prevalence of C allele of −572G > C polymorphism was significantly higher in patients than controls (Patients: 39.5%, Controls: 27.5%, p  = 0.011, χ 2 =6.463). Subjects with GC and CC genotype had significantly higher IL-6 levels than GG genotype ( p =<0.001). Patients with GC and CC genotype increased the DVT risk by 1.39 fold (OR a : 1.39, CI: 0.74–2.62) and 2.69 fold (OR a : 2.42, CI: 1.08–6.70), respectively. IL-6 −174G > C and −597G > A polymorphisms were not associated with raised IL-6 levels and nor with thrombotic risk (−174G > C: p  = 0.823 χ 2 =0.369; −597G > A: p  = 0.678 χ 2 =1.08). Conclusion: Our study emphasizes the importance of −572G > C polymorphism in increasing IL-6 levels, thereby showing its significant role in DVT in India. IL-6 −174G > C and −597G > A were neither associated with raised plasma IL-6 levels nor with thrombotic risk. Thus −572G > C polymorphism detection may be one of the connecting links between IL-6 and thrombotic risk in Indian DVT patients.